L’importanza dell’educazione musicale: risvolti pedagogici del fare bene musica insieme - Branca, Daniele (Studi sulla Formazione/Open Journal of Education, 2012)
Due to the limitations and the secular stagnation of traditional Musical Education, as well as the systematic neglect of Music in the Italian school, the article quotes scholars and summarizes the most advanced theories of the twentieth century, and traces the borders of today’s trial. This reveals that the important educational implications of making music together are: socialization, independence, creativity, identity, complexity. The music, far from being just technical practice, is configured as a universal tool of choice for an integrated learning.